Bentonite/Iron Oxide Composites: Preparation and Characterization by Hyperfine Methods. (16th July 2013) - Křišťan, Petr; Chlan, Vojtěch; Štěpánková, Helena; Řezníček, Richard; Kouřil, Karel; Štěpánek, Josef; Poláková, Kateřina; Procházka, Vít; Čuda, Jan; Medřík, Ivo
Abstract : Bentonite/iron oxide system is prepared by isothermal calcination of powder composed of bentonite clay and precursor containing ferric acetate. This preparation technique enables one to get the composite material directly, that is, iron oxide particles embedded in a bentonite matrix. Calcination temperature T calc is varied from 320°C to 700°C. The resulting series of samples is characterized by local methods based on hyperfine interactions: 57 Fe nuclear magnetic resonance (NMR) and the Mössbauer spectroscopy. The results show that the phase composition changes significantly in dependence on calcination temperature. The amount of maghemite phase rapidly increases up to T calc = 420 °C and decreases abruptly for T calc higher than 460°C.